PROFIL BENTUK TUBUH ORANG TUA DAN KEGEMUKAN SISWA DI SEKOLAH ADVENT SINGKAWANG - Sapti Widyarti Djula (Fakultas Ilmu Keperawatan Universitas Advent Indonesia, 2019)
When both parents are obese, thus the children are 80% potentially become overweight or obesity. If one of the parent is overweight or obesity, thus the children are 40% potentially to become overweight or obesity. The purpose of the study is to analyze is there any significant relationship between the parent's body shape with overweight among students at Singkawang Adventist School. The method of the study is descriptive with the quantitative method and the cross sectional design. The sampling technique is total sampling among the overweight students. Number of respondens is 35 persons which have been measure body height, body weight and determined Body Mass Index (BMI). Data processing using SPSS Program. The results of the study show that the status of overweight students is obesity and parentsâ€ body shape are overweight. There is no significant relationship between overweight students with parent's body shape. There is not enough evidence to refuse null hypothesis. Recommendation are given to Singkawang Adventist School Students in order to maintain a healthy lifestyle and give effort to reduce body weight. To the next researcher to do research with bigger sample size.